2009
DOI: 10.1002/pros.20906
|View full text |Cite
|
Sign up to set email alerts
|

Androgen ablation augments prostate cancer vaccine immunogenicity only when applied after immunization

Abstract: Background-Androgen ablation (AA) causes apoptosis of normal and neoplastic prostate cells. It is a standard treatment for advanced prostate cancer. Androgen ablation-mediated immunological effects include bone marrow hyperplasia, thymic regeneration, T and B cell lymphopoeisis and restoration of age-related peripheral T cell dysfunction. Androgens also regulate the transcription of several cytokines. Dendritic cells (DC) are the most potent antigen presenting cells that can activate antigen-specific naïve T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 60 publications
2
69
1
Order By: Relevance
“…The findings of this study are consistent with preclinical prostate cancer models (7,12) and a small randomized trial involving men with nonmetastatic castrate-resistant prostate cancer, in which survival was longer in patients vaccinated with a PSAencoding poxviral vaccine prior to second-line ADT (nilutamide) versus those receiving ADT prior to vaccination (13).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings of this study are consistent with preclinical prostate cancer models (7,12) and a small randomized trial involving men with nonmetastatic castrate-resistant prostate cancer, in which survival was longer in patients vaccinated with a PSAencoding poxviral vaccine prior to second-line ADT (nilutamide) versus those receiving ADT prior to vaccination (13).…”
Section: Discussionsupporting
confidence: 85%
“…ADT has been shown to augment antitumor immune responses in animal models (5-7) and in patients with prostate cancer (6,(8)(9)(10), especially when combined with immunotherapies (11). Several (but not all) studies have shown superior immunologic and antitumor responses when immunotherapy was administered prior to ADT (7,12,13). However, although there is a clear rationale for combining ADT with immunologic therapies in men with prostate cancer (14), optimal sequencing remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for a reciprocal potentiating action of ADT and immunotherapy is promising, but the results have not been convincing so far (33,41,42). Here, we have investigated the immune protection of combination treatment since having observed a promising synergistic effect of immunotherapy combined with orchiectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Using abiraterone in combination with sipuleucel-T would yield more immediate antitumor effects and thus allow time for the sipuleucel-T anticancer response to develop. Furthermore, suppression of testosterone has been demonstrated to have immunostimulatory properties (4)(5)(6)(7)(8)(9). Thus, reduction of testosterone levels with AA plus prednisone (AA þ P) may enhance the immunologic effects of sipuleucel-T. To date, because AA requires the coadministration of prednisone, which may have immunosuppressive effects, there is concern that this treatment could interfere with sipuleucel-T manufacture and/or dampen its immunologic effects if used in combination (10).…”
Section: Introductionmentioning
confidence: 99%